2017
DOI: 10.1097/dad.0000000000000807
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Toll-like Receptors in Human Oral Epithelium in Oral Lichenoid Reactions

Abstract: Oral lichenoid reactions (OLRs) are chronic inflammatory lesions induced by contact with allergens. Toll-like receptors (TLRs) are members of pattern-recognition receptor superfamily. Once activated, TLRs induce production of cytokines and chemokines, thus leading to inflammatory reaction in host tissue. In the present study, we aimed to investigate the potential role of TLRs in the initiation and perpetuation of OLRs, in which TLRs induce innate immune responses mounted against allergens. TLRs, 1 through 10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…It is noteworthy that TLR4 antibody significantly reduces the HMGB1‐mediated release of cytokines by immune cells, such as macrophages . Such highly upregulated TLR4 status in OLP lesions may indicate involvement of the HMGB1‐TLR4 axis in OLP, which may contribute to disease chronicity . However, the results should be interpreted with caution as TLR4 upregulation in OLP could also be ascribed to various DAMPs/pathogen‐associated molecular patterns (PAMPs) other than HMGB1 (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that TLR4 antibody significantly reduces the HMGB1‐mediated release of cytokines by immune cells, such as macrophages . Such highly upregulated TLR4 status in OLP lesions may indicate involvement of the HMGB1‐TLR4 axis in OLP, which may contribute to disease chronicity . However, the results should be interpreted with caution as TLR4 upregulation in OLP could also be ascribed to various DAMPs/pathogen‐associated molecular patterns (PAMPs) other than HMGB1 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The TLR4/MD‐2 complex is a vital component for HMGB1‐induced cytokine production and inflammation . Recently, we showed that TLR4 is upregulated in oral lichenoid lesions . It is noteworthy that TLR4 antibody significantly reduces the HMGB1‐mediated release of cytokines by immune cells, such as macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections (5 μm) that were obtained from OED and OTSCC patients and from healthy controls, were treated as described in our recent study [26]. The slides were incubated overnight in 1) 1 μg/ml rabbit anti-human polyclonal H 4 R antibody (LifeSpan Biosciences Inc., Seattle, WA, USA) and 1 μg/ml rabbit anti-human monoclonal mast cell tryptase antibody (Abcam, Cambridge, UK) at +4°C; 2) biotin-conjugated secondary antibodies (Vector Laboratories; 1:200) for 1 h; 3) avidin-biotinperoxidase complex (Vector Laboratories; 1:200) for 1 h; 4) diaminobenzidine tetrahydrochloride for 10 min.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
“…This is in accordance to Ohno et al [8] who revealed high expression in basal keratinocytes of the normal buccal mucosa. This finding could be explained by Salem et al [25] who pointed out that the outmost epithelial layers depend on their junctional attachments for defense not needing to express TLRs whereas the deeper basal cells use their TLRs to provide immunologic backup.…”
Section: Discussionmentioning
confidence: 99%